Stimuli for Adaptations in Muscle Length and the Length Range of Active Force Exertion—A Narrative Review - Kruse, Annika; Rivares, Cintia; Weide, Guido; Tilp, Markus; Jaspers, Richard T. (Frontiers in Physiology, 2021)
Treatment strategies and training regimens, which induce longitudinal muscle growth and increase the muscles’ length range of active force exertion, are important to improve muscle function and to reduce muscle strain injuries in clinical populations and in athletes with limited muscle extensibility. Animal studies have shown several specific loading strategies resulting in longitudinal muscle fiber growth by addition of sarcomeres in series. Currently, such strategies are also applied to humans in order to induce similar adaptations. However, there is no clear scientific evidence that specific strategies result in longitudinal growth of human muscles. Therefore, the question remains what triggers longitudinal muscle growth in humans. The aim of this review was to identify strategies that induce longitudinal human muscle growth. For this purpose, literature was reviewed and summarized with regard to the following topics: (1) Key determinants of typical muscle length and the length range of active force exertion; (2) Information on typical muscle growth and the effects of mechanical loading on growth and adaptation of muscle and tendinous tissues in healthy animals and humans; (3) The current knowledge and research gaps on the regulation of longitudinal muscle growth; and (4) Potential strategies to induce longitudinal muscle growth. The following potential strategies and important aspects that may positively affect longitudinal muscle growth were deduced: (1) Muscle length at which the loading is performed seems to be decisive, i.e., greater elongations after active or passive mechanical loading at long muscle length are expected; (2) Concentric, isometric and eccentric exercises may induce longitudinal muscle growth by stimulating different muscular adaptations (i.e., increases in fiber cross-sectional area and/or fiber length). Mechanical loading intensity also plays an important role. All three training strategies may increase tendon stiffness, but whether and how these changes may influence muscle growth remains to be elucidated. (3) The approach to combine stretching with activation seems promising (e.g., static stretching and electrical stimulation, loaded inter-set stretching) and warrants further research. Finally, our work shows the need for detailed investigation of the mechanisms of growth of pennate muscles, as those may longitudinally grow by both trophy and addition of sarcomeres in series.